Calling activity and vocal repertoire of hypsiboas prasinus (Anura, Hylidae), a treefrog from the atlantic forest of Brazil - Delgado, Danilo Bareâ [UNESP]; Haddad, Célio F.B. [UNESP] (Herpetologists League, 2015)
Vocalizations are important for female attraction and territory delimitation in prolonged breeding anurans. Males of Hypsiboas prasinus display year-round nocturnal calling activity, using herbaceous and bushy vegetation along the margins of ponds as calling sites. We monitored the temporal pattern of calling activity from July 2011 to June 2012, and vocalizations were recorded for bioacoustical analysis. We quantified the physical parameters for four of the five types of vocalizations found in this species: an introductory advertisement call (Type A call), a chorus advertisement call (Type B call), a resuming activity advertisement call (Type C call), and an agonistic call. Calling activity was spread throughout the annual cycle and there was no correlation between air temperature and calling activity. This finding indicates that the calling pattern is controlled predominantly by behavior and not physiology. During the cold dry season, some individuals were observed to shift their calling sites to the water surface, causing vocalizations to be lower pitched and longer.
Keywords: Activity pattern; Annual cycle; Bioacoustics; Burmeister's Treefrogs; Serra do Japi; Vocalization